Risk of Arterial Ischemic Events After Intracerebral Hemorrhage. Issue 1 (January 2020) - Murthy, Santosh B.; Diaz, Ivan; Wu, Xian; Merkler, Alexander E.; Iadecola, Costantino; Safford, Monika M.; Sheth, Kevin N.; Navi, Babak B.; Kamel, Hooman
Abstract : Background and Purpose—: The risk of arterial ischemic events after intracerebral hemorrhage (ICH) is poorly understood given the lack of a control group in prior studies. This study aimed to evaluate the risk of acute ischemic stroke and myocardial infarction (MI) among patients with and without ICH. Methods—: We performed a retrospective cohort study using claims data from Medicare beneficiaries from 2008 to 2014. Our exposure was acute ICH, identified using validated International Classification of Diseases, Ninth Revision, Clinical Modification diagnosis codes. Our primary outcome was a composite of acute ischemic stroke and MI, whereas secondary outcomes were ischemic stroke alone and MI alone. We used Cox regression analysis to compute hazard ratios during 1-month intervals after ICH. Sensitivity analyses entailed exclusion of patients with atrial fibrillation and valvular heart disease. Results—: Among 1 760 439 Medicare beneficiaries, 5924 had ICH. The 1-year cumulative incidence of an arterial ischemic event was 5.7% (95% CI, 4.8–6.8) in patients with ICH and 1.8% (95% CI, 1.7–1.9) in patients without ICH. After adjusting for potential confounders, the risk of an arterial ischemic event remained significantly increased for the first 6 months after ICH and was especially high in the first month (hazard ratio, 6.7 [95% CI, 5.0–8.6]). In secondary analysis, the risk of ischemic stroke was increased in the first 6 months after ICH (hazard ratio, 6.1 [95% CI, 3.5–9.3]) but the risk of MI was not (hazard ratio, 1.6 [95% CI, 0.3–2.9]). In sensitivity analyses excluding patients with atrial fibrillation and valvular heart disease, the association between ICH and arterial ischemic events was similar to that of the primary analysis. Conclusions—: In a large population-based cohort, we found that elderly patients with ICH had a substantially increased risk of ischemic stroke in the first 6 months after diagnosis. Further exploration of this risk is needed to determine optimal secondary prevention strategies for these patients. Abstract : Supplemental Digital Content is available in the text.